Sexual Crime and the Profile of Perpetrators in Aydın - Dirlik, Musa; Özkök, Mustafa Selim; Katkıcı, Ufuk; Erel, Özlem (The Bulletin of Legal Medicine, 2002)
In this study, we aimed to determine the characteristic of victims and assailants in sexual assault. We analysed 554 sexual offence cases, which had been concluded on Aydın Courts, between 1996-2001. All cases were evaluated according to year distributions, kind of offence, victims and assailants age groups, occupation of assailants, and decision of court. The age range for the victims was 3-85 years and mean age was 17.68+9.80 yaers, for assailants the age range was 11-71 years and mean age was 25.66+10.04 years. The half of the assailants were self employed and they were, accusedof rape. Abduction and anal intercourse victims had the lowest mean age. In 208 cases, the accused received punishmentwhile in 181 cases the acquitlet. In 145 cases punishment of the assailant for rap crime is postponed, because the victim and accused got married so the article 434 of Turkish Criminal Law as applied. Key words: Sexual assault, assailants, court decisions.